Swiss expert opinion: current approaches in faecal microbiota transplantation in daily practice (Swiss Medical Weekly, 2023)
INTRODUCTION: Faecal microbiota transplantation (FMT) is an established therapy for recurrent C. difficile infection, and recent studies have reported encouraging results of FMT in patients with ulcerative colitis. Few international consensus guidelines exist for this therapy, and thus FMT policies and practices differ among European countries. As of 2019, stool transplants are considered a non-standardised medicinal product in Switzerland, and a standardised production process requires authorisation by the Swiss Agency for Therapeutic Products. This authorisation leads to prolonged administrative procedures and increasing costs, which reduces treatment accessibility. In particular, patients with ulcerative colitis in Switzerland can only benefit from FMT off-label, even though it is a valid therapeutic option. Therefore, this study summarised the available data on FMT and established a framework for the standardised use of FMT.METHODS: A panel of Swiss gastroenterologists with a special interest in inflammatory bowel disease was established to identify the current key issues of FMT. After a comprehensive review of the literature, statements were formulated about FMT indications, donor screening, stool transplant preparation and administration, and safety aspects. The panel then voted on the statements following the Delphi process; the statements were reformulated and revoted until a consensus was reached. The manuscript was then reviewed by an infectiologist (the head of Lausanne’s FMT centre).RESULTS: The established statements are summarised in the supplementary tables in the appendix to this paper. The working group hopes these will help standardise FMT practice in Switzerland and contribute to making faecal microbiota transplantation a safe and accessible treatment for patients with recurrent C. difficile infections and selected patients with ulcerative colitis, as well as other indications in the future.